Wireless sensor networks for healthcare applications - Dishongh, Terrance J. (Artech House, 2010)
"Unlike other books on wireless sensors networks, this unique reference focuses on methods of application, validation and testing based on real deployments of sensor networks in the clinical and home environments. Key topics include healthcare and wireless sensors, sensor network applications, designs of experiments using sensors, data collection and decision making, clinical deployment of wireless sensor networks, contextual awareness medication prompting field trials in homes, social health monitoring, and the future of wireless sensor networks in healthcare."--Publisher description